Parenting Styles of Chinese Immigrant Parents and Personal Development of Chinese Immigrants’ Children in Ireland From the Perspective of Psychology of Education - Zan, Luyan (Trinity College (Dublin, Ireland). School of Education, 2022)
Immigration is a major life event (Chen et al., 2019). It could completely change one’s life, breaking away from the original living environment, missing support from family and friends, and adapting to a new culture (Chen et al., 2019). The purpose of this thesis is to study the living conditions, educational and psychological development and challenges of Chinese immigrants and their children in Ireland. This thesis uses a combination of online questionnaires and interviews to study the mental health and personal development of Chinese immigrants children and the Chinese immigrant parents’ educational philosophy and parenting styles for their children. Thirty-two parents completed the questionnaires, and three parents took part in the interview. According to the Strengths and Difficulties Questionnaire (SDQ), the emotional symptoms, conduct problems, hyperactivity-inattention and prosocial behaviour of Chinese immigrant children in Ireland are at normal levels. However, conduct problems are at high risk, and peer problems are at an abnormally high. Furthermore, Chinese immigrant children are obedient to their parents, respect their elders, and are able to consider the feelings of others. According to the interviews, there are three main types of parenting styles and educational philosophies of Chinese immigrant parents, the first is the traditional Chinese parenting style, the second is the combination of Chinese and Western parenting styles, and the third is the Western-style education philosophy. Parenting style is related to the interviewees’ education level and life experience and is also influenced by traditional Chinese Confucianism. More programs should be to support Chinese immigrant children in Ireland, such as English proficiency training and peer relationship building. However, the questionnaire and interview data are limited in this research, resulting in the limited accuracy and credibility of the research conclusions. More questionnaires and interviews are needed in the subsequent investigation and in-depth research in the future.
Keywords: Psychology of Education; Education